So, anyway ... - Cleese, John.; Cleese, John. (New York : Crown Archetype, 2014)
In this rollicking memoir, Cleese takes his readers on a Grand Tour of his ascent in the entertainment world, from his humble beginnings in a sleepy English town and his early comedic days at Cambridge University (with future Python partner Graham Chapman), to the founding of the landmark comedy troupe that would propel him to worldwide renown.
Includes index.
Includes bibliographical references and index.
Keywords: Motion picture actors and actresses -- Great Britain -- Biography